Parvovirus B19 Infection Mimicking Autoimmune Hepatitis: A Brief Report - Mathur, Kartikeya; Singh, Satyam Kumar; Kumar, Prawin; Goyal, Jagdish; Agarwal, Divya; Birda, Chhagan Lal; Agarwal, Ashish (Journal of Gastrointestinal Infections, 2024)
Background Parvovirus B19 can cause a variety of manifestations, mainly in children but occasionally in adults. Parvovirus hepatitis is an uncommon manifestation and is usually mild and self-limited. Parvovirus-related acute severe hepatitis and fulminant hepatitis, including acute liver failure, are rare presentations and can mimic other common causes of hepatitis. We hereby report a case of parvovirus-related severe hepatitis in adolescent girls.Case Report A 17-year-old girl presented with fever and upper respiratory symptoms, followed by onset of jaundice. Her general and systemic physical examinations were unremarkable except for pallor and icterus. On evaluation, she had severe anemia and hepatocellular pattern of jaundice (the maximum value of total bilirubin was 53, and aspartate and alanine transaminase were 756 and 256, respectively). The etiological workup revealed negative markers for typical viral hepatitis. Still, the autoimmune profile revealed a positive antinuclear antibody, and her liver biopsy was also consistent with autoimmune hepatitis. Because of severe anemia and the absence of other hepatic decompensation, systemic viral illness with hepatic involvement was considered, and workup in the same line revealed parvovirus serology positivity. A final diagnosis of parvovirus-related acute severe hepatitis with aplastic crisis was considered, and she was managed with a short course of oral steroids. She responded well to treatment; clinical and biochemical parameters showed improvement on subsequent follow-up. Even after a prolonged follow-up of 1.5 years, she is in clinical and biochemical remission, further confirming the diagnosis of parvovirus-related acute hepatitis.Conclusion Parvovirus can cause severe hepatitis and should be considered in the differential diagnosis of hepatitis of unknown etiology, especially if there is concomitant hematological involvement.
Keywords: acute severe hepatitis; parvovirus hepatitis; autoimmune hepatitis; case report